Epidemiological studies of stripe rust of wheat caused by Puccinia striiformis - V.K. RAZDAN, B.C. SHARMA, DEEPAK KHER; ATUL KUMAR, ARUN KHAJURIA, VISHAL GUPTA* (Indian Phytopathology, 2016)
The effect of epidemiological factors such as minimum temperature, maximum temperature, maximum relative humidity, minimum relative humidity, rainfall, soil temperature, canopy temperature evaporation, cloud cover (morning and evening), wind speed, sunshine hours, vapour pressure (morning and evening) and crop age on the severity of stripe rust in four wheat varieties (RSP 561, HD 2967, Agra Local and PBW 343), under normal sowing condition was studied during rabi 2013-14 and 2014-15. The disease appeared in all the tested wheat varieties,53 days after sowing, in the first standard meteorological week (SMW), in both the rabi seasons. Sharp increase in disease severity was observed during 6th to 8th SMW due to the conducive weather conditions which prevailed during the previous fortnight. The predictive models generated through stepwise multiple regressions analysis revealed that thermic, hydric and light variables contributed significantly for variance in disease severity of Â stripe rust in selected wheat varieties.